A convenient route for the preparation of peptide nucleic acid monomers carrying acid-labile groups for the protection of the amino function - Ferrer, Elisenda; Eisenhut, Michael; Eritja, Ramon (Letters in peptide science, 1999)
A convenient route for the preparation of peptide nucleic acid (PNA) monomers is described. Two different baselabile protecting groups (2-cyanoethyl and 4-nitrophenylethyl) are described for the protection of the carboxylic function of theN-(2-aminoethyl)glycine backbone during the assembly of the monomers. These groups are selectively removed yielding the desired PNA monomers in high yields, the 2-cyanoethyl group being faster and cleaner than the 4-nitrophenylethyl group. The use of PNA monomers for the preparation of DNA-PNA chimeric molecules is also discussed.
Gesehen am 09.02.2021